Perception of guidance counseling and engagement with the role of guidance counselor among senior high school students in selected private schools in the city of Binan, Laguna - Ilumin, Alex (Technium Social Sciences Journal, 2025)
Guidance counseling is crucial in supporting the academic, emotional, and social development of Senior High School (SHS) students, especially as they face career choices and personal challenges (Gysbers & Henderson, 2020; ASCA, 2020). While its impact on academic and emotional outcomes is recognized, less is known about how students perceive and engage with guidance services—particularly in private school settings where cultural attitudes and access may vary (Lapan, 2020). This study aimed to examine students’ perceptions and levels of engagement with guidance counselors in selected private SHS in Biñan, Laguna. The study utilized a descriptive-correlational design and surveyed SHS students from selected private schools in Biñan, Laguna. Data was gathered through questionnaires focused on demographics, perceptions of guidance counseling, and engagement levels. The theoretical framework was anchored on Social Cognitive Career Theory (SCCT), emphasizing how personal beliefs and contextual factors influence career-related behaviors. The study revealed that most respondents were female, Roman Catholic, and from middle-income families, with household heads primarily employed in the private sector or owning businesses. Students generally held a favorable perception of guidance counseling, with an average weighted mean of 3.44. However, their level of engagement with guidance counselors was low, reflected in a mean score of 1.95, indicating limited participation, especially in one-on-one counseling sessions. Statistical analysis showed that economic status significantly influenced students' perceptions of guidance counseling (p<0.05), with middle-income students reporting more favorable views, while gender and religion had no significant impact. In terms of engagement, there were no notable differences across all demographic variables. Importantly, a significant positive correlation was found between students’ perceptions of and their engagement with guidance counselors (p<0.05), suggesting that students with more positive perceptions were more likely to engage with counseling services. These findings informed the creation of a targeted action plan aimed at improving students' perceptions and increasing engagement with guidance services in private SHS settings in Biñan, Laguna. The study concludes that while students recognize the value of guidance counseling, they seldom engage deeply with it. Economic status influences how students perceive these services, with middle-income students generally showing more favorable attitudes. Lack of engagement may be due to misconceptions or limited accessibility. Addressing these gaps through targeted programs, inclusive policies, and improved counselor-student interaction is recommended. A contextualized action plan for private schools in Biñan, Laguna was proposed to enhance guidance services and student well-being.